Методика моніторінгу інноваційної діяльності - Погорєлов, Ігор Миколайович; Погорєлов, Микола Іванович (НТУ "ХПІ", 2016)
Прагнення до підвищення ефективності діяльності підприємств, зміцнення ринкових позицій, зниження рівня невизначеності в постачанні і збуті інноваційної продукції стали основними передумовами використання моніторингу в системі інноваційного розвитку підприємства. Концепція інноваційного розвитку дозволяє підприємству добиватися поставлених цілей в умовах динамічного, еволюціонуючого середовища.

The aspiration to increase of efficiency of activity of enterprises, strengthen market positions, reducing the level of uncertainty in the supply and marketing of innovative products were the main prerequisites for the use of monitoring in the system of innovative development of the enterprise. The concept of innovation development allows businesses to achieve their goals in a dynamic, evolving environment. Studying the existing in the economic literature approaches to the definition of monitoring gives the opportunity to assert that it has no unambiguous interpretation, because it is used in various spheres of scientific and practical activities.
The method of monitoring of innovation activity
Keywords: діяльність підприємства; контроль; управління; інформаційне забезпечення; експертиза; процеси суспільного життя; збалансована система показників; стратегічне управління; methodology; activities; research; analysis; monitoring; novac